Ultra-high static magnetic field induces a change in the spectrum but not frequency of DNA spontaneous mutations in Arabidopsis thaliana - Xu, Xiang; Chen, Mengjiao; Chen, Tianli; Ni, Xinda; Fang, Zhicai; Fang, Yanwen; Zhang, Lei; Zhang, Xin; Huang, Jirong (Frontiers in Plant Science, 2023)
Biological effects of magnetic fields have been extensively studied in plants, microorganisms and animals, and applications of magnetic fields in regulation of plant growth and phytoprotection is a promising field in sustainable agriculture. However, the effect of magnetic fields especially ultra-high static magnetic field (UHSMF) on genomic stability is largely unclear. Here, we investigated the mutagenicity of 24.5, 30.5 and 33.0 T UHSMFs with the gradient of 150, 95 and 0 T/m, respectively, via whole genome sequencing. Our results showed that 1 h exposure of Arabidopsis dried seeds to UHSMFs has no significant effect on the average rate of DNA mutations including single nucleotide variations and InDels (insertions and deletions) in comparison with the control, but 33.0 T and 24.5 T treatments lead to a significant change in the rate of nucleotide transitions and InDels longer than 3 bp, respectively, suggesting that both strength and gradient of UHSMF impact molecular spectrum of DNA mutations. We also found that the decreased transition rate in UHSMF groups is correlated with the upstream flanking sequences of G and C mutation sites. Furthermore, the germination rate of seeds exposed to 24.5 T SMF with -150 T/m gradient showed a significant decrease at 24 hours after sowing. Overall, our data lay a basis for precisely assessing the potential risk of UHSMF on DNA stability, and for elucidating molecular